Immunoglobulin G4-Related Periaortitis Complicated by Aortic Rupture and Aortoduodenal Fistula after Endovascular AAA Repair. (August 2014) - Kasashima, Satomi; Kawashima, Atsuhiro; Kasashima, Fuminori; Endo, Masamitsu; Matsumoto, Yasushi; Kawakami, Kengo; Kayahara, Masato; Ohta, Hajime; Yano, Masaaki; Marukawa, Youhei
Purpose: To report a rare and complicated case of immunoglobulin (Ig) G4-related periaortitis involving both the aortic wall and the retroperitoneum without aneurysmal formation. Case Report: A 79-year-old man with IgG4-related periaortitis suffered aortic rupture despite a normal caliber aorta after 6 months of steroid therapy (20 mg/d). Endovascular repair with an aortic cuff sealed the rupture. Steroid therapy was halted 2 weeks later due to infection. Four months later, a biopsy during esophagogastroduodenoscopy to investigate gastrointestinal bleeding suggested a relapse of IgG4-RD in the duodenum. Subsequent aortoduodenal fistula formation proved fatal. Generally, IgG4-related periaortitis does not result in such complications due to the absence of aneurysm formation and a thick aortic wall. Conclusions: Our report highlights a rare case of IgG4-related periaortitis where complications resulted following steroid therapy and surgical intervention, emphasizing the difficulties in dealing with IgG4-related cardiovascular lesions.